2016
DOI: 10.1002/jor.23405
|View full text |Cite
|
Sign up to set email alerts
|

In vivo kinematics of knee replacement during daily living activities: Condylar and post-cam contact assessment by three-dimensional fluoroscopy and finite element analyses

Abstract: In total knee replacement, the investigation on the exact contact patterns at the post-cam in implanted patients from real in vivo data during daily living activities is fundamental for validating implant design concepts and assessing relevant performances. This study is aimed at verifying the restoration of natural tibio-femoral condylar kinematics by investigating the post-cam engagement at different motor tasks. An innovative validated technique, combining three-dimensional fluoroscopic and finite element a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 50 publications
3
18
0
Order By: Relevance
“…4,19 Belvedere et al recently reported that anterior contact occurred in 40-60% of patients after JOURNEY I at knee extension during chair-rising, stair-climbing, and step-up. 20 Anterior cam-post contact after JOURNEY II BCS TKA was relatively low in this study during squatting (14%) and stair-climbing (27%) near extension. This finding suggests that the cam-post design for the JOURNEY II BCS TKA could result in lower cam-post stresses, thus reducing the risk for failure of the tibial post.…”
Section: Discussionmentioning
confidence: 51%
“…4,19 Belvedere et al recently reported that anterior contact occurred in 40-60% of patients after JOURNEY I at knee extension during chair-rising, stair-climbing, and step-up. 20 Anterior cam-post contact after JOURNEY II BCS TKA was relatively low in this study during squatting (14%) and stair-climbing (27%) near extension. This finding suggests that the cam-post design for the JOURNEY II BCS TKA could result in lower cam-post stresses, thus reducing the risk for failure of the tibial post.…”
Section: Discussionmentioning
confidence: 51%
“…Modern finite element models are usually based on medical scans and possess a high accuracy of anatomical realism fundamental for the development of appropriate, reliable and effective tools aimed at supporting clinically-tailored questions 1 . Besides the simulation of the native joints, models are widely used for the prediction of the effects of degenerative pathologies, traumatic events as well as surgical repair and replacement strategie [2][3][4][5][6][7][8] . In particular, they are used for subject-specific analyses and for guiding the surgical pre-planning phase by comparing the effect of different designs of knee prostheses on the same patient [9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…34,[36][37][38][39][40][41] In fact, after small technical adaptations, VFA can still be used to measure PFJ kinematics, as well as under loading conditions typical of daily living. [36][37][38]40 The general aim of this study was to analyze quantitatively the extent to which postoperative PFJ kinematics assessed at 6 months of follow-up after TKA mimics the intraoperative kinematics after final component implantation. The hypothesis is that intraoperative kinematics assessment of PFJ, as well as TFJ, after final component implantation is capable of predicting postoperative knee kinematics after TKA during activities of daily living.…”
mentioning
confidence: 99%